Synthesis and Evaluation of Mannich Bases of 2-(Benzimidazolylaminomethyl) thiazolidin-4-one as Antimicrobial Agents - SRIVASTAVA, PANKAJ; M. VARSHNEY, MUNENDRA; KUMAR, DHEERAJ; SISODIA, PRIYANKA (Asian Journal of Chemistry, 2010)
Mannich bases of 2-(benzimidazolylaminomethyl) thiazolidin-4-one are synthesized by amination at position 5 using formaldehyde and various secondary amines. The prepared compounds have been characterized by physico-chemical and spectral analysis and screened for their antibacterial activity.